2016
DOI: 10.3201/eid2211.160414
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies to Severe Fever with Thrombocytopenia Syndrome Virus 4 Years after Hospitalization, China

Abstract: Severe fever with thrombocytopenia syndrome is an emerging hemorrhagic fever disease in eastern Asia, caused by a tickborne bunyavirus. Of 25 patients hospitalized with this disease in China, 100% produced and maintained neutralizing antibodies to severe fever with thrombocytopenia syndrome virus for the study period of 4 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 14 publications
(16 reference statements)
1
26
1
Order By: Relevance
“…The presence of antibody to SFTSV in an individual is considered as evidence of past SFTSV infection. In the cases of recovery from SFTS infection, antibody possessing neutral activity against SFTSV has been reported even 4 years after the viral infection . In the present study, no antibody‐positive samples indicating a history of SFTSV infection were found among 3990 donations obtained from the Chugoku‐Shikoku district in Japan.…”
Section: Discussioncontrasting
confidence: 45%
“…The presence of antibody to SFTSV in an individual is considered as evidence of past SFTSV infection. In the cases of recovery from SFTS infection, antibody possessing neutral activity against SFTSV has been reported even 4 years after the viral infection . In the present study, no antibody‐positive samples indicating a history of SFTSV infection were found among 3990 donations obtained from the Chugoku‐Shikoku district in Japan.…”
Section: Discussioncontrasting
confidence: 45%
“…Studies have shown that neutralizing antibodies against SFTSV surface glycoprotein (glycoprotein N, Gn) are highly associated with patient survival (11)(12)(13). Our previous study in a patient cohort demonstrated that the presence of serum anti-Gn antibodies was correlated with survival, while the mortality of SFTS patients without serum anti-Gn antibodies was as high as 66.7% (14).…”
Section: Introductionmentioning
confidence: 90%
“…Recent studies have shown that 100% of SFTS confirmed cases produce neutralizing antibodies to SFTSV and can last for four years with a decrease in titers 17 . We also performed a follow-up study of eight people with neutralizing antibodies in 2014 and 2017.…”
Section: Discussionmentioning
confidence: 99%